2020
DOI: 10.1113/jp279655
|View full text |Cite
|
Sign up to set email alerts
|

Beetroot juice lowers blood pressure and improves endothelial function in pregnant eNOS−/− mice: importance of nitrate‐independent effects

Abstract: Key points Maternal hypertension is associated with increased rates of pregnancy pathologies, including fetal growth restriction, due at least in part to reductions in nitric oxide (NO) bioavailability and associated vascular dysfunction. Dietary nitrate supplementation, from beetroot juice (BRJ), has been shown to increase NO bioavailability and improve cardiovascular function in both preclinical and clinical studies. This study is the first to investigate effects of dietary nitrate supplementation in a preg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
34
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 57 publications
1
34
0
3
Order By: Relevance
“…### P < 0.001 eNOS −/− vs. WT; *P < 0.05 GSEP vs. H 2 O. N = 6-11 dams per group. the current study are consistent with our own data (Tropea et al, 2020) and those reported by others (Hefler et al, 2001;Poudel et al, 2013). Administration of a different polyphenol, resveratrol (3,5,4 -trihydroxystilbene), was reported to have no effect on SBP in eNOS −/− mice (Poudel et al, 2013).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…### P < 0.001 eNOS −/− vs. WT; *P < 0.05 GSEP vs. H 2 O. N = 6-11 dams per group. the current study are consistent with our own data (Tropea et al, 2020) and those reported by others (Hefler et al, 2001;Poudel et al, 2013). Administration of a different polyphenol, resveratrol (3,5,4 -trihydroxystilbene), was reported to have no effect on SBP in eNOS −/− mice (Poudel et al, 2013).…”
Section: Discussionsupporting
confidence: 93%
“…Administration of a different polyphenol, resveratrol (3,5,4 -trihydroxystilbene), was reported to have no effect on SBP in eNOS −/− mice (Poudel et al, 2013). In contrast, our recent data demonstrated that supplementation with beetroot juice significantly lowered SBP in eNOS −/− mice, effects which we believe are potentially attributable to bioactive phytochemicals contained within the juice, including polyphenols and flavonoids (Tropea et al, 2020), in common with the active constituents of GSEP. The phenolic content of the extract used in the current study has been reported to be 94% and mostly made of polymers of catechin (Edirisinghe et al, 2008;Sivaprakasapillai et al, 2009), shown to provide a higher antioxidant ability compared to other commonly used antioxidants (Bagchi et al, 1997(Bagchi et al, , 1998.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…The study reported in The Journal of Physiology by Tropea et al (2020) examined the effects of BRJ on blood pressure (BP) and endothelial function in pregnant endothelial nitric oxide synthase knockout mice (eNOS −/− ). eNOS is one of three NOS isoforms and the eNOS −/− mouse model is well established with respect to assessing maternal hypertension as related to fetal growth restriction (FGR) and vascular dysfunction (Tropea et al 2020). During pregnancy, NO maintains the low-resistance/high-flow environment of the utero-placental vascular system.…”
mentioning
confidence: 99%